The Effect of Principal's Academic Supervision, Work Environment and Work Commitment on Teacher Performance at Public Middle Schools in Jekan Raya District - Sisi Aulia Fitri; Wiwik Wijayanti (Journal of Educational Sciences, 2026)
This study examines the effect of principals’ academic supervision, the work environment, and work commitment on teacher performance in public Middle schools in Jekan Raya District. A quantitative approach with an ex post facto design was employed. The population consisted of 143 teachers, all of whom were included as the total sample. Data were collected using a validated and reliable questionnaire. The analysis used simple regression and multiple linear regression after meeting prerequisite tests, including normality, linearity, multicollinearity, and heteroscedasticity. The results indicate that principals’ academic supervision has a positive and significant effect on teacher performance, contributing 47.7%. The work environment also positively and significantly affects teacher performance with a contribution of 57.2%. Likewise, work commitment has a positive and significant effect, contributing 47.0%. Simultaneously, principals’ academic supervision, the work environment, and work commitment significantly influence teacher performance with a contribution of 68.1% (R² = 0.681; Sig. = 0.000). These findings indicate that improving teacher performance can be achieved through consistent academic supervision, a supportive work environment, and stronger teacher work commitment in carrying out professional responsibilities at school.